The Quality and Challenges of Catholic Education among Parochial Schools in the Diocese of Kabankalan - Marlon Tejada; Dennis V. Madrigal (Philippine Social Science Journal, 2021)
Catholic education is a Catholic school’s way of participating in the Church’s evangelizing mission through holistic formation and conversion accordant with Catholic faith and doctrines. This descriptive comparative-correlational study determined the quality of Catholic education among parochial schools relative to the Philippine Catholic Schools Standards (PCSS) domains: Catholic identity and mission, leadership and governance, learner development, learning environment, and operational vitality. The 252 school personnel and 36 administrators of 18 parochial schools in the Diocese of Kabankalan, Philippines, for the School Year 2020-2021, answered the standardized PCSS survey questionnaire. The results showed that parochial schools are excellent relative to the offering of quality Catholic education. The findings also showed no significant difference in the level of quality of Catholic education among parochial schools when respondents are grouped according to designation and length of service. In addition, the quality of Catholic education does not correlate with the school budget and size.